An enhanced media ciphertext-policy attribute-based encryption algorithm on media cloud - Hao Li; Lianbing Deng; Cheng Yang; Jianbo Liu (International Journal of Distributed Sensor Networks)
With the development of cloud computing, more and more video services are moving to the cloud. How to realize fine-grained access control of those data on cloud becomes an urgent problem. Attribute-based encryption provides a solution. However, heavy computation is still a bottleneck restricting the wider application of attribute-based encryption in cloud computing. In addition, we find that expression of the access control structure on media cloud can be further improved. To solve these problems, we propose an enhanced media ciphertext-policy attribute-based encryption algorithm and introduce its two key components, the multiple access tree and the key chain. To increase the scalability of the proposed algorithm, we discussed the issues of multi-authorization, user revocation, and 1 − n multiple access tree. Security analysis shows that enhanced media ciphertext-policy attribute-based encryption can successfully resist chosen-plaintext attacks under the decisional bilinear Diffie–Hellman assumption. Performance analysis proves both theoretically and practically that the proposed algorithm incurs less computational cost than the traditional ciphertext-policy attribute-based encryption, multi-message ciphertext-policy attribute-based encryption, and scalable ciphertext-policy attribute-based encryption by optimizing the access control structure. Our proposed algorithm has strong practical significance in media cloud.